RECOVERY OF AN OXISOL DEGRADED BY THE CONSTRUCTION OF A HYDROELECTRIC POWER PLANT - Carvalho, Joseane Carina Borges De; Espindola, Carlos Roberto; Alves, Marlene Cristina; Figueiredo, Getulio Coutinho; Dechen, Sonia Carmela Falci (Sociedade Brasileira de Ciência do Solo, 2015)
ABSTRACT The removal of thick layers of soil under native scrubland (Cerrado) on the right bank of the Paraná River in Selvíria (State of Mato Grosso do Sul, Brazil) for construction of the Ilha Solteira Hydroelectric Power Plant caused environmental damage, affecting the revegetation process of the stripped soil. Over the years, various kinds of land use and management systems have been tried, and the aim of this study was to assess the effects of these attempts to restore the structural quality of the soil. The experiment was conducted considering five treatments and thirty replications. The following treatments were applied: stripped soil without anthropic intervention and total absence of plant cover; stripped soil treated with sewage sludge and planted to eucalyptus and grass a year ago; stripped soil developing natural secondary vegetation (capoeira) since 1969; pastureland since 1978, replacing the native vegetation; and soil under native vegetation (Cerrado). In the 0.00-0.20 m layer, the soil was chemically characterized for each experimental treatment. A 30-point sampling grid was used to assess soil porosity and bulk density, and to assess aggregate stability in terms of mean weight diameter (MWD) and geometric mean diameter (GMD). Aggregate stability was also determined using simulated rainfall. The results show that using sewage sludge incorporated with a rotary hoe improved the chemical fertility of the soil and produced more uniform soil pore size distribution. Leaving the land to develop secondary vegetation or turning it over to pastureland produced an intermediate level of structural soil quality, and these two treatments produced similar results. Stripped soil without anthropic intervention was of the lowest quality, with the lowest values for cation exchange capacity (CEC) and macroporosity, as well as the highest values of soil bulk density and percentage of aggregates with diameter size <0.50 mm, corroborated by its lower organic matter content. However, the percentage of larger aggregates was higher in the native vegetation treatment, which boosted MWD and GMD values. Therefore, assessment of some land use and management systems show that even decades after their implementation to mitigate the degenerative effects resulting from the installation of the Hydroelectric Plant, more efficient approaches are still required to recover the structural quality of the soil.

RESUMO A retirada de espessas camadas de solo sob cerrado nativo da margem direita do rio Paraná, em Selvíria, MS, para a construção da Usina Hidrelétrica de Ilha Solteira, provocou degradação ambiental, com reflexos no processo de revegetação do solo decapitado. Esse local foi submetido às tentativas de usos e manejos diversificados ao longo dos anos, constituindo o objetivo deste trabalho avaliar o efeito das abordagens aplicadas à recuperação da qualidade estrutural do solo. O experimento foi realizado considerando cinco tratamentos e 30 repetições. Os tratamentos experimentais consistiram em: solo degradado (decapitado), sem intervenção antrópica e com ausência de cobertura vegetal; solo degradado, tratado com lodo de esgoto e cultivado com eucalipto e gramínea há um ano; solo degradado, mantido com capoeira em regeneração natural desde o ano de 1969; solo com pastagem desde 1978, em substituição à vegetação nativa; e solo sob vegetação nativa (Cerrado). A caracterização química do solo para cada tratamento experimental foi realizada na camada de 0,00-0,20 m. Uma grade de amostragem com 30 pontos foi utilizada para avaliar a porosidade e densidade do solo e os índices de estabilidade de agregados diâmetro médio ponderado (DMP) e diâmetro médio geométrico (DMG). A estabilidade de agregados foi também determinada com chuva simulada. Os resultados evidenciaram que a utilização de lodo de esgoto incorporado com enxada rotativa melhorou a fertilidade química e promoveu distribuição mais equilibrada do tamanho de poros do solo. Os tratamentos com capoeira e pastagem apresentaram nível intermediário de qualidade estrutural do solo, sendo mais similares entre si. A qualidade do solo degradado e sem intervenção antrópica foi a mais prejudicada, havendo valores menores de capacidade de troca catiônica e macroporosidade, bem como valores maiores de densidade do solo e de porcentagem de agregados com diâmetros <0,50 mm, corroborados pelo seu menor teor de matéria orgânica. Já o porcentual de agregados de tamanhos maiores foi mais expressivo no tratamento sob vegetação nativa, o que refletiu positivamente nos valores de DMP e DMG. Portanto, mesmo decorridas várias décadas da implantação de alguns dos sistemas de uso e manejo avaliados, para mitigar os efeitos deletérios advindos da instalação dessa Usina Hidrelétrica, ainda são necessárias abordagens mais eficientes para recuperar a qualidade estrutural do solo.
RECUPERAÇÃO DE UM LATOSSOLO DEGRADADO PELA IMPLANTAÇÃO DE UMA USINA HIDRELÉTRICA
Keywords: aggregate stability; soil compaction; stripped soil; soil quality; estabilidade de agregados; compactação; solo decapitado; qualidade do solo